Evaluation of biorationals against thrips (Sdothrips cardamomi Ramk.) and shoot and capsule borer (Conogethes punctiferalis Guen.) in cardamom - Backiyarani, M Murugan, A Joseph Rajkumar, P Sainamole Kurian, S (Journal of Spices and Aromatic Crops, 2002)
A field experiment was conducted to evaluate the efficacy of biorationals in the management of thrips and shoot and capsule borer of cardamom. Among the biorationals evaluated, fish oil insecticidal soap (FOIS) (Na) 2.5% + tobacco extract 2.5% significantly reduced the damage caused by thrips. None of the treatments is effective for the control of shoot and capsule borer infestation on the capsules and all the treatments were on par with the control. Spraying quinalphos (0.05%) reduced the damage caused by thrips (6%) and increased the yield (391 g plant-1). Foraging activity of honey bees was highest in control plots.